Reduction, rationality and game theory in Marxian economics - Philp, Bruce, 1968- (Routledge frontiers of political economy ;, 2005)
The main areas of interest in Marxian economics are examined, paying particular attention to class conflict, analytical Marxism and game theory and will be of interest to a wide variety of economists and social scientists.